Argumentation and Decision Making in Professional Practice. Issue 4 (1st October 2016) - Gainsburg, Julie; Fox, John; Solan, Lawrence M.
Abstract : How is argumentation used in professional practice? As schools aim to ensure that students are college-and-career ready, classroom practices might be informed by argumentation in the professions. An analysis of evidence-based reasoning in 3 professions—engineering, law, and medicine—offers out-of-school perspectives on the practices and purposes of argumentation. In these fields, sound argumentation is crucial to successful real-world decision making: Is this building design sound? What is the best course of action for this patient? How should this lawsuit be decided? This article brings the role of professional judgment to the fore, as well as professional norms and values in the construction of arguments in the professions. Similarities and contrasts in argumentation and decision making across the 3 professions are drawn.